Detection to Hospital Door: Gender Differences of Patients With Acute Stroke Symptoms - Walter, Silke; Phillips, Daniel; Wells, Brittany; Moon, Robert; Bertsch, Thomas; Grunwald, Iris Q.; Fassbender, Klaus (Frontiers in Neurology, 2022)
Prehospital stroke management is challenging however crucial part of the acute stroke chain to enable equal access to available highly specialised stroke care. It involves a critical understanding of players usually not specialised in acute stroke treatments. There is contradictory information about gender inequity in prehospital stroke detection, dispatch and delivery to hospital stroke centres. The aim of this narrative review is to summarise knowledge of gender differences in these first three stages of acute stroke management. Information on the detection of acute stroke symptoms by patients, their relatives and bystanders is discussed. Women seem to have a better overall knowledge about stroke although general understanding needs to be improved. However, older age and different social situations of women could be identified as reasons for reduced and delayed help-seeking. Dispatch and delivery lie within the responsibility of the emergency medical service. Differences in clinical presentation with symptoms mainly affecting general conditions could be identified as a crucial challenge leading to gender inequity in these stages. Improvement of stroke education strategies has to be applied to tackle this inequal management. However, specifically designed projects and analyses are needed to understand more details of sex differences in prehospital stroke management, which is a necessary first step for the potential development of substantially improving strategies.